Teacher Assessment and Its Relation to the Planning of Mathematics Teaching - Suharjo Suharjo (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 1998)
The aim of this study were to identify the implementation of teacher assessment in primary mathematics and the implementation of planning in primary mathematics teaching, and to examine the relationship between the results of teacher assessment and planning in the teaching of primary mathematics. This study was conducted in two primary schools in North of London. Four teachers from each school were involved in completing the questionnaire and interview. The results indicated that there were four models of relationship between teacher assessment and the planning of mathematics teaching: the teacher assessed the children to see their level of understanding, assessed the children in a systematic and continous process, related the results of assessment to the planning of mathematics teaching on a daily basis, and related the results of assessment to their planning of mathematics teaching in the long-term (half-termly basis).